Genetic characteristics of coxsackievirus A16 associated with hand, foot, and mouth disease in Nanjing, China - Wei Yong; Mengkai Qiao; Limin Shi; Xuan Wang; Yan Wang; Xuefei Du; Min He; Jie Ding (Journal of Infection in Developing Countries)
Introduction: Coxsackievirus A16 (CVA16) is a main pathogen in hand, foot, and mouth disease (HFMD) worldwide. This study intended to clarify the genetic characteristics of CVA16 associated with HFMD in a defined area in Nanjing, China. Methodology: A total of 175 CVA16 strains isolated from throat swabs between 2011 and 2013 were obtained through sentinel hospitals in Nanjing. Multiplex polymerase chain reaction (PCR) was used to amplify the VP1 sequence of local CVA16 strains, and their genetic relationship with 138 CVA16 strains isolated in China and other countries of the world was compared. Results: Phylogenetic analysis based on complete VP1 sequences revealed that subgenotype B1a and B1b were predominantly circulating in Nanjing and B1b strains were spread more widely. The evolution of CVA16 strains is very conservative, with a mean distance of less than 9%. Moreover, six reported conservative regions in VP1 protein were examined, and three of them exhibited high conservation in all CVA16 genotypes except the G-10 prototype and may serve for further vaccine research. Conclusions: The CVA16 strains circulating in Nanjing, China, in 2011 to 2013 belonged to different genotypes and evolved in a conservative way. To provide further evidence for epidemiological linkage and evolutionary recombination events in CVA16, persistent surveillance of HFMD-associated pathogens is required.